RELIGIOUS MODERATION THROUGH PERSIA-ACEH INTERCULTURAL COMMUNICATION - Usman, Abdul Rani; Sulaiman, Azman; Fauzan, Ahmad; Zulyadi, Teuku; Salahuddin, Afrizal; Putri, Nanda; Jannah, Maisal; Misra, Laini (Islam Futura, 2024)
The cultural encounter between Aceh and Persian traditions occurred through the approach of Sufism during the early spread of Islam in the Nusantara, where Islam was embraced as a socio-cultural ideology by the Acehnese people. The formalization of structural Islamic law in Aceh today has effectively closed off the possibility of religious moderation within the diversity of new cultural expressions. One of these measures is the establishment of Shafi'i school regulations as the main model in Aceh, which impacts the restriction and adjustment of certain traditions and arts that do not align with this school of thought. As a result, intercultural communication becomes an alternative approach to rebuilding mutual understanding, emphasizing the importance of tolerance, and appreciating cultural differences in Indonesia. However, the desired form of moderation has not yet materialized, as evidenced by the emergence of coercive attitudes within a singular religious perspective. Through an intercultural communication approach, this study reveals the moderation attitudes manifested from the cultural encounter between Aceh and Persia. The presence of Persian-style gravestones, still visible in several areas of Pidie (such as Giging, Bungiy, Meunasah Raya Paleue, and Cot Satu), serves as evidence of this cultural exchange. The descriptive-analytical method employed in this research uncovers several findings, including that history demonstrates the intense cultural communication between Persia and the Acehnese people as an expression of religious moderation. However, over time, with the implementation of structural Islam, the attitude of religious moderation has gradually eroded, either directly or indirectly.